2015
DOI: 10.1177/0165025415584808
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of allocentric spatial memory resolution in children from 2 to 4 years of age

Abstract: Allocentric spatial memory, the memory for locations coded in relation to objects comprising our environment, is a fundamental component of episodic memory and is dependent on the integrity of the hippocampal formation in adulthood. Previous research from different laboratories reported that basic allocentric spatial memory abilities are reliably observed in children after 2 years of age. Based on work performed in monkeys and rats, we had proposed that the functional maturation of direct entorhinal cortex pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…Our recent work at the genetic and neuroanatomical levels revealed that different hippocampal regions mature at different times during development (Favre, Banta Lavenex, & Lavenex, 2012a, 2012bJabès, Banta Lavenex, Amaral, & Lavenex, 2010Lavenex, Banta Lavenex, & Amaral, 2007;Lavenex, Sugden, Davis, Gregg, & Banta Lavenex, 2011). These findings, together with our studies of the development of human spatial memory (Ribordy, Jabès, Banta Lavenex, & Lavenex, 2013;Ribordy Lambert, Lavenex & Banta Lavenex, 2015), support the hypothesis that the differential maturation of distinct hippocampal circuits might underlie the differential emergence of specific ''hippocampus-dependent'' memory processes, culminating in the emergence of adult-like episodic memory concomitant with the maturation of all hippocampal circuits . This is a view shared by Jabès and Nelson (2015).…”
Section: Hippocampussupporting
confidence: 59%
“…Our recent work at the genetic and neuroanatomical levels revealed that different hippocampal regions mature at different times during development (Favre, Banta Lavenex, & Lavenex, 2012a, 2012bJabès, Banta Lavenex, Amaral, & Lavenex, 2010Lavenex, Banta Lavenex, & Amaral, 2007;Lavenex, Sugden, Davis, Gregg, & Banta Lavenex, 2011). These findings, together with our studies of the development of human spatial memory (Ribordy, Jabès, Banta Lavenex, & Lavenex, 2013;Ribordy Lambert, Lavenex & Banta Lavenex, 2015), support the hypothesis that the differential maturation of distinct hippocampal circuits might underlie the differential emergence of specific ''hippocampus-dependent'' memory processes, culminating in the emergence of adult-like episodic memory concomitant with the maturation of all hippocampal circuits . This is a view shared by Jabès and Nelson (2015).…”
Section: Hippocampussupporting
confidence: 59%
“…Indeed, 70% of the indivuals with WS that we tested were incapable of solving our task, which can be considered the most basic of place (Ribordy, Jabes, Banta Lavenex, & Lavenex, 2013;Ribordy Lambert, Lavenex, & Banta Lavenex, 2015).…”
Section: Hippocampal Place Learningmentioning
confidence: 99%
“…The offset of infantile amnesia, when children become capable of long-term encoding of some, albeit few, episodic memories, occurs around 2 years of age (Newcombe et al, 2007;Rubin, 2000). Similarly, basic allocentric spatial memory abilities are reliably observed in children after 2 years of age (Newcombe, Huttenlocher, Bullock Drummey, & Wiley, 1998;Ribordy et al, 2013, Ribordy Lambert et al, 2015.…”
mentioning
confidence: 99%
“…In a series of experiments by Ribordy et al (2013) and Ribordy Lambert et al (2015), children were asked to find rewards hidden beneath cups in an open-field arena, over repeated trials. The simplest version of this task required children to learn and remember one rewarded location among four potentially rewarded locations.…”
mentioning
confidence: 99%
See 1 more Smart Citation